2017
DOI: 10.1088/2399-6528/aa9b0e
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of cooperation in a coupled socio-ecological system through a direct or an indirect social control mechanism

Abstract: The successful management of a common pool resource (CPR) by its social agents is key to its sustainability. In order to maintain the ecological resource of such a coupled socio-ecological system, cooperative effort from the whole society is required and this necessitates proper social control mechanism to regulate the social order. In this paper, we explore the effects of two social control mechanisms: ostracism and voluntary enforcement, on agents that actively exploit the CPR within societies of different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Conceptually similar conclusion can also be obtained when ostracism is introduced as a collective control mechanisms into another coupled social-resource model proposed by Tavoni et al [15]. It is found that the stationary state of cooperators and defectors does not only depend on the ostracism strength, but also on the resource inflow [33]. We thus conclude that when we design a social control mechanism to solve the overexploitation problem in a coupled social-resource system we should first pay attention to the intrinsic features of the system which can determine in advance whether the designed control mechanism is capable to drive the level of common resource toward the desired direction.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Conceptually similar conclusion can also be obtained when ostracism is introduced as a collective control mechanisms into another coupled social-resource model proposed by Tavoni et al [15]. It is found that the stationary state of cooperators and defectors does not only depend on the ostracism strength, but also on the resource inflow [33]. We thus conclude that when we design a social control mechanism to solve the overexploitation problem in a coupled social-resource system we should first pay attention to the intrinsic features of the system which can determine in advance whether the designed control mechanism is capable to drive the level of common resource toward the desired direction.…”
Section: Discussionsupporting
confidence: 77%
“…In this more realistic model of a coupled social-resource system, we further introduce a top-down-like control mechanism that serves to block overexploitation of the common resource. This control mechanism is not only motivated by theoretical works or lab experiments [20,33,46], but is also stimulated by realistic field investigations focusing on the forest commons management [34,47]. In contrast to a bottom-up self-regulation this top-down-type control assumes an effective external monitoring of agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This consideration of the enforcement strategy as a voluntary enforcement involves a more complex three-strategy system. Indeed, this is a kind of a bottom-up self-regulation for influencing the evolution of cooperation ( Sugiarto et al., 2017 ). We stress that this approach is different from the top-down-like incentive mechanism used in previous works ( Chen et al., 2015 ; Góis et al., 2019 ), in which cooperators can be rewarded and defectors can be punished directly by external centralized institutions.…”
Section: Discussionmentioning
confidence: 99%